Stanniocalicin 2 suppresses breast cancer cell migration and invasion via the PKC/claudin-1-mediated signaling. - Jing Hou; Ziliang Wang; Han Xu; Lina Yang; Xiaoli Yu; Zhaozhi Yang; Yun Deng; Jiao Meng; Yan Feng; Xiaomao Guo; Gong Yang (PLoS ONE, 2015)
Stanniocalcin (STC), a glycoprotein hormone, is expressed in a wide variety of tissues to regulate Ca2+ and PO4- homeostasis. STC2, a member of STC family, has been reported to be associated with tumor development. In this study, we investigated whether the expression of STC2 is associated with migration and invasion of breast cancer cells. We found that breast cancer cell line 231 HM transfected with STC2 shRNA displayed high motility, fibroblast morphology, and enhanced cell migration and invasion. Introduction of STC2 in 231 cells reduced cell migration and invasion. In response to irradiation, silencing of STC2 in 231 HM cells reduced apoptosis, whereas overexpression of STC2 in 231 cells promoted apoptosis, compared with in control cells. Mechanistic study showed that STC2 negatively regulated PKC to control the expression of Claudin-1, which subsequently induced the expressions of EMT-related factors including ZEB1, ZO-1, Slug, Twist, and MMP9. Suppression of PKC activity by using a PKC inhibitor (Go 6983) restored the normal motility of STC2-silenced cells. Furthermore, in vivo animal assay showed that STC2 inhibited tumorigenesis and metastasis of breast cancer cells. Collectively, these results indicate that STC2 may inhibit EMT at least partially through the PKC/Claudin-1-mediated signaling in human breast cancer cells. Thus, STC2 may be exploited as a biomarker for metastasis and targeted therapy in human breast cancer.